PREVALENCE OF ß-THALASSEMIA MUTATIONS AMONG NORTHEASTERN IRANIAN POPULATION AND THEIR IMPACTS ON HEMATOLOGICAL INDICES AND APPLICATION OF PRENATAL DIAGNOSIS, A SEVEN-YEARS STUDY - Mohammad Ehsan Jaripour; Kourosh Hayatigolkhatmi; Vahid Iranmanesh; Farhad Khadivi Zand; Zahra Badiei; Hamid Farhangi; Ali Ghasemi; Abdollah Banihashem; Reza Jafarzadeh Esfehani; Ariane Sadr-Nabavi (Mediterranean Journal of Hematology and Infectious Diseases)
Background and objective: ß-thalassemia results from a diverse range of mutations inside the hemoglobin subunit β (HBB) gene. In a study of β-thalassemia carriers and some of their at-risk fetuses in the Khorasan province of Iran we aimed to recognize the most common mutations in the region and to find a possible link between these mutations and some of the relevant hematological indices.